Gendersensibler Philosophie- und Ethikunterricht. Standortbestimmung, Desiderate und Diskussionen - Albus, Vanessa (Selbstverständnisse der Philosophiedidaktik zwischen Fachphilosophie und Interdisziplinarität)

Evaluation eines Lehrmoduls zur Stärkung der Demokratiebildungskompetenz von Lehramtsstudierenden - Wehde, Janis (die hochschullehre)
In diesem Beitrag wird ein zwei Sitzungen umfassendes, flexibel integrierbares Lehrmodul zur Stärkung der Demokratiebildungskompetenz von Lehramtsstudierenden evaluiert. Dazu werden 101 schriftliche Reflexionen von Studierenden aus drei bildungswissenschaftlichen Hochschulseminaren aus dem Wintersemester 2022/2023 und dem Sommersemester 2023 anhand der Text-Sortier-Technik ausgewertet. Die Evaluationsergebnisse verdeutlichen die studentischen Lernaktivitäten in den Kompetenzbereichen Werte, Einstellungen und Fähigkeiten für eine demokratische Kultur. Zudem wurden die Kenntnisse der Studierenden zur methodischen Gestaltung von demokratischen Aushandlungsprozessen im Unterrichts- und Schulkontext erweitert. Demnach konnte die Wirksamkeit des Lernmoduls auf der Prozess- und Ergebnisdimension hochschulischen Lernens plausibilisiert werden.

KI außer Kontrolle - Hälterlein, Jens (AUSDRUCK - Das IMI-Magazin)

Analyzing Symmetries of Swarms of Mobile Robots Using Equivariant Dynamical Systems - Gerlach, Raphael; von der Gracht, Sören (arXiv:2503.07576)
In this article, we investigate symmetry properties of distributed systems of mobile robots. We consider a swarm of n robots in the OBLOT model and analyze their collective Fsync dynamics using of equivariant dynamical systems theory. To this end, we show that the corresponding evolution function commutes with rotational and reflective transformations of R^2. These form a group that is isomorphic to O(2) x S_n, the product group of the orthogonal group and the permutation on n elements. The theory of equivariant dynamical systems is used to deduce a hierarchy along which symmetries of a robot swarm can potentially increase following an arbitrary protocol. By decoupling the Look phase from the Compute and Move phases in the mathematical description of an LCM cycle, this hierarchy can be characterized in terms of automorphisms of connectivity graphs. In particular, we find all possible types of symmetry increase, if the decoupled Compute and Move phase is invertible. Finally, we apply our results to protocols which induce state-dependent linear dynamics, where the reduced system consisting of only the Compute and Move phase is linear.
Keywords: dynamical systems; coupled systems; distributed computing; robot swarms; autonomous mobile robots; symmetry; equivariant dynamics

Tarnschriften als Widerstandsgattung der diskursiven Disruption - Markewitz, Friedrich (Discourses in/of Disruption)
Clashes of heterogeneous discourses are conceptualized differently within the various strands of discourse research. To simplify, one can speak of synthesizing positions of merging discourses on the one hand and difference-based positions of heterogeneous discourses on the other. The latter position, which goes far beyond intra- and extradiscursive conflicts that can ultimately be resolved, can be related to Jean-Francois Lyotard‘s reflections on the incommensurability of discourses: Starting from an understanding that every discourse has certain inner-discursive rules and that when heterogeneous discourses meet, these rules come into conflict, questions arise about the possibilities and limits of how different discourses deal with each other and their potential incommensurability. The challenges of the encounters between heterogeneous discourses can be comprehensively and productively examined during the ‚Third Reich‘ and in relation to the genre of resistance ‚Tarnschrift‘. In these camouflage writings, heterogeneous discourses collide in a confined textual space, as the camouflage text corresponded to the rules of the prevailing Nazi discourse and the camouflaged text embedded in it corresponds to the rules of resistance discourses. This textual juxtaposition of communicative expressions of different discourses allows us to analyse procedures of discursive disruption, irritation and incommensurability. Starting from a perspective based on Lyotard‘s considerations, camouflage writings are therefore to be analysed and reflected upon as a genre of discursive disruption
Keywords: camouflage writing; incommensurability; "third reich"; resistance

Vision: Towards True User-Centric Design for Digital Identity Wallets - Last, Yorick; Arias Cabarcos, Patricia (Symposium on Usable Security and Privacy (USEC) 2025)
To facilitate the growing demand for a universal means of digital identification across services, while preserving user control and privacy, multiple digital identity implementations have emerged. From a technical perspective, many of these rely on established concepts within cryptography, allowing them to provide benefits in terms of security and privacy. Recent legislation also promises broader recognition and acceptance of digital identities, both in the digital world and beyond. However, research into the usability, accessibility, and user understanding of digital identities is rare. We argue that the development of usable digital identity wallets is vital to the successful and inclusive application of digital identities in society. In this vision paper, we describe our research plans for obtaining a better understanding of how to develop these usable digital identities wallets.

ReconOS64 - Hardware-Software Multithreading for Heterogeneous Platform FPGAs - Clausing, Lennart
Heterogeneous computing devices comprising multiple processing systems combined with a programmable logic like an FPGA have become increasingly popular. Developing and runtime managing these heterogeneous platform devices, however, still poses multiple challenges. The programming paradigms for hardware and software applications fundamentally differ, while the runtime management requires additional attention. The first steps towards unifying design flows have been taken by creating high-level synthesis tools. However, these toolsfocus on the design process and lack runtime management features. FPGA operating systems aim to close this gap by providing runtime management features and build tools. ReconOS, as an example of an FPGA operating system, allows bridging the hardware-software gap by integrating hardware-located computation units as threads into a host operating system, allowing for familiar inter-thread programming paradigms to be extended to FPGAs. This thesis presents ReconOS64, a successor and fork of ReconOS, aiming at modern 64-bit platform systems-on-chip. Besides establishing support for this platform and incorporating new system generation processes, ReconOS64 provides additional features for both development and runtime management. By providing a flexible grouping mechanism for hardware-located threads, partial reconfiguration for exchanging individual threads at runtime is simplified. Further runtime flexibility was achieved by implementing a multi-clock architecture, allowing individual groups of threads to be executed at different frequencies, which can be adapted during runtime with a low reconfiguration overhead. In addition, this thesis provides an overview of further development approaches on various systems based on ReconOS64 and ReconOS.

Blogpost: "Berlin als Jewish Space? Perspektiven der jüdischen Gegenwartsliteratur" - Spener, Anna Maria

Muhammad as a Prophet of Late Antiquity: The Anti-Apocalyptic Nature of Muhammad’s Prophetic Wisdom - Ghaffar, Zishan (Theology of Prophecy in Dialogue: A Jewish-Christian-Muslim Encounter)

Theology of Prophecy in Dialogue: A Jewish-Christian-Muslim Encounter
This volume examines the Rabbinic, Qur’anic and Christian understandings of prophecy from a historical and comparative theological perspective. The Rabbinic perspectives on the phenomenon of prophecy are analyzed in their historical continuity and engagement with the theological traditions of Islam and Christianity. The examination of female prophecy also occupies a central place here. Similarly, several contributors describe the deep roots of Qur’anic prophetology in the Christian and Jewish traditions of Late Antiquity and the Arabic context. Finally, the anthology attempts to reflect on these different theological traditions of prophecy in the Christian, Jewish, and Qur’anic traditions from a comparative theological perspective and to discuss the possible theological significance of this phenomenon in the modern age.

Emotionsreflexion als Element universitären Lehrens und Lernens Emotional reflection as an element of university teaching and learning - Lehberger, Regine (Zeitschrift für Hochschulentwicklung)
Fähigkeiten zur Wahrnehmung und Regulation von Emotionen sind von besonderer Relevanz für Studierende, da Fördermaßnahmen im Bereich der Emotionsregulation auch positive Effekte auf die Studienqualität, den Studienerfolg und die allgemeine Persönlichkeitsentwicklung haben können. Jedoch wird diesem Thema wenig Aufmerksamkeit geschenkt und hochschuldidaktisch steht die Gestaltung von kognitiven und inhaltsbezogenen Lernarrangements im Zentrum. Die Einbindung von Gelegenheiten zur Emotionsreflexion in die Lehre bietet eine niederschwellige Maßnahme zur Förderung emotionaler Kompetenzen, weshalb im vorliegenden Beitrag ein Instrument zur Umsetzung dieser Aufgabe vorgeschlagen wird.
Keywords: Emotionsreflexion; Studierende; Hochschullehre; Reflexion

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)

Statistics and data science education as a vehicle for empowering citizens – short summary of a survey - Biehler, Rolf; Kawakami, Takashi; Lampen, Erna; Weiland, Travis; Zapata-Cardona, Lucía (European Mathematical Society Magazine)
This article is a short summary of the report of survey team 3, presented to the 15th International Congress on Mathematical Education (ICME-15) in Sydney in July 2024.

Transcription in Computing Education Research: A Review and Recommendations - Terfloth, Lutz; Lohmer, Vivien; Kern, Friederike; Schulte, Carsten (Informatics in Education)
Transcripts play a crucial role in qualitative research in computing education, with significant implications for the credibility and reproducibility of findings. However, unreflective and inconsistent transcription standards may unintentionally introduce biases, potentially undermining the validity of research outcomes and the collective progress of the field. In this article, we introduce transcription as a theoretically guided process rather than a mere preparatory step, illustrating its role using a case example. Additionally, through a systematic review of 107 qualitative research articles in computing education, we identify widespread shortcomings in the reporting and implementation of transcription practices, revealing a need for greater intentionality and transparency. To address these challenges, we propose a three-step framework for selecting, applying, and documenting transcription standards that align with the specific context and goals of a study. Rather than advocating for overly complex, one-size-fits-all transcription strategies, we emphasize the importance of a context-appropriate approach that is clearly communicated to foster trust and reproducibility. By advancing a more robust transcription culture, this work aims to support computing education researchers in adopting standards that enhance the quality and reliability of qualitative research in the field.

Kollegiales Feedback in der Hochschullehre - Osthushenrich, Judith (Praxishandbuch Hochschullehre II - Bewertung, Digitalisierung und Barrierefreiheit)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Machine learning of continuous and discrete variational ODEs with convergence guarantee and uncertainty quantification - Offen, Christian (Mathematics of Computation)
The article introduces a method to learn dynamical systems that are governed by Euler–Lagrange equations from data. The method is based on Gaussian process regression and identifies continuous or discrete Lagrangians and is, therefore, structure preserving by design. A rigorous proof of convergence as the distance between observation data points converges to zero and lower bounds for convergence rates are provided. Next to convergence guarantees, the method allows for quantification of model uncertainty, which can provide a basis of adaptive sampling techniques. We provide efficient uncertainty quantification of any observable that is linear in the Lagrangian, including of Hamiltonian functions (energy) and symplectic structures, which is of interest in the context of system identification. The article overcomes major practical and theoretical difficulties related to the ill-posedness of the identification task of (discrete) Lagrangians through a careful design of geometric regularisation strategies and through an exploit of a relation to convex minimisation problems in reproducing kernel Hilbert spaces.

Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Soft and Constrained Hypertree Width - Lanzinger, Matthias; Okulmus, Cem; Pichler, Reinhard; Selzer, Alexander; Gottlob, Georg (Proceedings of the ACM on Management of Data)
Hypertree decompositions provide a way to evaluate Conjunctive Queries (CQs) in polynomial time, where the exponent of this polynomial is determined by the width of the decomposition. In theory, the goal of efficient CQ evaluation therefore has to be a minimisation of the width. However, in practical settings, it turns out that there are also other properties of a decomposition that influence the performance of query evaluation. It is therefore of interest to restrict the computation of decompositions by constraints and to guide this computation by preferences. To this end, we propose a novel framework based on candidate tree decompositions, which allows us to introduce soft hypertree width (shw). This width measure is a relaxation of hypertree width (hw); it is never greater than hw and, in some cases, shw may actually be lower than hw. Most importantly, shw preserves the tractability of deciding if a given CQ is below some fixed bound, while offering more algorithmic flexibility. In particular, it provides a natural way to incorporate preferences and constraints into the computation of decompositions. A prototype implementation and preliminary experiments confirm that this novel framework can indeed have a practical impact on query evaluation.

Towards Practicable Algorithms for Rewriting Graph Queries Beyond DL-Lite - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (The Semantic Web - 22nd European Semantic Web Conference, ESWC 2025, Portoroz, Slovenia, June 1-5, 2025, Proceedings, Part I)
Despite the advantages that the virtual knowledge graph paradigm has brought to many application domains, state-of-the-art systems still do not support popular graph database management systems like Neo4j. Their query rewriting algorithms focus on languages like conjunctive queries and their unions, which were developed for relational data and are poorly suited for graph data. Moreover, they also limit the expressiveness of the ontology languages that admit rewritings, restricting them to those that enjoy the so-called FO-rewritability property. Rewritings have thus focused on the DL-Lite family of Description Logics. In this paper, we propose a technique for rewriting a family of navigational queries for a suitably tailored fragment of ELHI. Leveraging navigational features in the target query language, we can include some widely-used axiom shapes not supported by DL-Lite. We implemented a proof-of-concept prototype that rewrites into Cypher queries, and tested it on a real-world cognitive neuroscience use case with promising results.
Keywords: Ontology-based Data Access; Property Graphs; Navigational Queries

Lessons Learned from the ProDaBi Project: Shaping Perspectives at the Intersection of Data, AI, and Education Towards Fostering AI and Data Science Literacy in Schools Across Disciplines. - Biehler, Rolf; Schulte, Carsten (Proceedings of the 1st Symposium on Integrating AI and Data Science into School Education Across Disciplines (AIDEA 1 2025), Salzburg, Austria)